2003
DOI: 10.1074/jbc.m310425200
|View full text |Cite
|
Sign up to set email alerts
|

Lysine-Phosphatidylcholine Adducts in Kringle V Impart Unique Immunological and Potential Pro-inflammatory Properties to Human Apolipoprotein(a)

Abstract: Lipoprotein(a), Lp(a), an athero-thrombotic risk factor, reacts with EO6, a natural monoclonal autoantibody that recognizes the phophorylcholine (PC) group of oxidized phosphatidylcholine (oxPtdPC) either as a lipid or linked by a Schiff base to lysine residues of peptides/proteins. Here we show that EO6 reacts with free apolipoprotein(a) apo(a), its C-terminal domain, F2 (but not the N-terminal F1), kringle V-containing fragments obtained by the enzymatic digestion of apo(a) and also kringle V-containing apo(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
107
1
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(121 citation statements)
references
References 29 publications
10
107
1
3
Order By: Relevance
“…The above results are also supported by the studies about ox-PL, which have demonstrated convincingly that a key ox-PL is preferentially associated with Lp(a) [52] and correlates with both the presence and extent of angiographically documented CAD [40,53], and their concentrations increase after ACS [51] and immediately after PCI [54].…”
Section: The Clinical Value Of Circulating Oxidized Lp(a)supporting
confidence: 72%
“…The above results are also supported by the studies about ox-PL, which have demonstrated convincingly that a key ox-PL is preferentially associated with Lp(a) [52] and correlates with both the presence and extent of angiographically documented CAD [40,53], and their concentrations increase after ACS [51] and immediately after PCI [54].…”
Section: The Clinical Value Of Circulating Oxidized Lp(a)supporting
confidence: 72%
“…26 We have recently shown that kringle V of apo(a) covalently binds Ϸ2 moles of OxPL detected by antibody E06 and that this portion of apo(a) induced IL-8 production by macrophages. 26 We recently demonstrated that both OxLDL-E06 and Lp(a) rise concurrently after acute coronary syndromes, but unlike the present study, in which levels increased only after PCI in otherwise uncomplicated procedures, levels remained elevated up to 3 to 6 months.…”
Section: Tsimikas Et Al Oxldl and Lp(a) In Pci 3167mentioning
confidence: 99%
“…26 We have recently shown that kringle V of apo(a) covalently binds Ϸ2 moles of OxPL detected by antibody E06 and that this portion of apo(a) induced IL-8 production by macrophages. 26 We recently demonstrated that both OxLDL-E06 and Lp(a) rise concurrently after acute coronary syndromes, but unlike the present study, in which levels increased only after PCI in otherwise uncomplicated procedures, levels remained elevated up to 3 to 6 months. 11 In the present study, we documented for the first time a transient disassociation of OxLDL-E06 and Lp(a) in the post-PCI samples, suggesting that these two compounds are independently generated to some extent but later reassociate.…”
Section: Tsimikas Et Al Oxldl and Lp(a) In Pci 3167mentioning
confidence: 99%
“…In a series of studies, Witztum et al have demonstrated convincingly that a key oxidized phospholipid is preferentially associated with Lp(a). [117][118][119] Proinflammatory, oxidized phospholipids are covalently bound to kringle V in apo(a), a portion of apo(a) associated with macrophage IL-8 production. 117 These results suggest that Lp(a) may act as a preferential acceptor that tightly binds oxidized phospholipids transferred from tissues or from other lipoproteins.…”
Section: Oxidized Phospholipids: Relation To Lp(a)mentioning
confidence: 99%
“…[117][118][119] Proinflammatory, oxidized phospholipids are covalently bound to kringle V in apo(a), a portion of apo(a) associated with macrophage IL-8 production. 117 These results suggest that Lp(a) may act as a preferential acceptor that tightly binds oxidized phospholipids transferred from tissues or from other lipoproteins. 119 This could imply that Lp(a) functions as a scavenger absorbing potentially deleterious oxidized lipids, preventing an increased uptake in the vessel wall of other lipoproteins, primarily LDL, containing this factor.…”
Section: Oxidized Phospholipids: Relation To Lp(a)mentioning
confidence: 99%